The Comparison of Motoric Characteristics of Young Soccer Players According to Their Playing Positions - Ayşegül Yapıcı; Eray Aydın; Eylem Çelik; Gizem Başkaya (ümit doğan üstün, 2016)
The purpose of this study was to compare motoric features, 10-30m speed, agility, flexibility, standing long jump and yo-yo 1 test according to playing position at young soccer players. 36 football players (Xage: 18.13 ± 0.88 year, Xheight: 175.13±11.58 cm, Xweight: 65.68 ± 11.52 kg) from the Denizlispor clup participated voluntarily in this study. 10-30m speed, agility, flexibility, standing long jump and yo-yo 1 test were applied. In yo-yo 1 test was measured in distance which is covered by players. The other performance tests measurements were given two trial and took the best score. The data are reported as means and standard deviations. Data were analyzed using a one-way analysis of variance (ANOVA) with repeated measures, posthoc comparisons by using Tukey's "honestly significantly different" test for pair wise comparisons. The statistical significance was set at p<0.05. When compared midfield and forward players' between 30m speed test statistically significantly difference was found (p<0.05). Defender and midfield players' between yo-yo 1 test and defender and forward players' between yo-yo 1 test measurement statistically significantly difference was found (p<0.05). Defender and midfield players between zigzag test statistically significantly difference was found (p<0.05). The findings of the present study indicated that motoric features according to playing position (defender-midfield-forward) at young soccer players' values were important in order to inform the trainer for development about team's performance.